FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI UNTUK BERKARIR SEBAGAI KONSULTAN PAJAK (Studi Mahasiswa Akuntansi: PTN dan PTS Pekanbaru) - Harun Haposan; Kirmizi Kirmizi; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study is to examine the effects of motivation, consideration of employment market, perception, professional recognition and social values to the career interest of accounting students to become a tax consultant. The datas were gained from the polls filled by accounting students in four university in Pekanbaru. The sampling is selected using purposive sampling, data collection method using a questionnaire with the number of sample of this research was 306 studentsand were able to be processed with double linear regression by using SPSS 21. The results of this study showed that motivation, consideration of employment market, perception, professional recognition and social values affected the career interest of accounting students to be working as tax consultant. The value of coefficient determination (R2) was 0,551 which showed that 55,1% variables of workin career interest can be explained by variable of motivation, consideration of employment market, perception, professional recognition and social values. And the rest of 44,9% can be explained by other variables which not included in this research.Keywords: Career interest, Motivation, Consideration Of Employment Market, Perception, Professional Recognition, Social Values